Under the Radar: Regulatory Collaborations and their Selective Use to Facilitate Organizational Compliance - Desai, Vinit M. (Academy of Management Journal, 2016)
Why do organizations vary in complying with regulatory mandates? While some may resist these pressures, what to change or how to change it may be unclear even when managers do intend to fully comply. Though scarce in the literature, theories regarding how organizations search for and learn from information under uncertainty provide an ideal window through which to examine organizational responses to regulatory mandates and other external pressures. In this study, I adapt these theories to posit that organizations establish close collaborative relationships with regulatory agents to overcome uncertainty following enforcement actions, and I ascertain that such collaborations can enhance organizational compliance with enforced mandates. However, I also find that organizations with the least visible practices will go “under the radar,” foregoing such collaborations because of the risks associated with disclosing private information to regulators. Thus, paradoxically, those organizations that could arguably learn or change the most through these exchanges in fact eschew them. This study and its findings deepen our understanding regarding organizational compliance with external pressures, emphasize the role of organizational visibility in interactions with outside agents, and contribute to the literatures on organizational search and learning by examining a reciprocal learning process.